The Influence of E-Leadership, School Culture, Teacher Cooperation, and Teacher Self-Efficacy on Teacher Performance: The Context of Indonesia - Elfina, Ira; Hendra, Robi (FKIP Universitas Jambi, 2025)
This study investigates the influence of leadership, school culture, teacher cooperation, and teacher self-efficacy on teacher performance in Indonesian primary schools. Using a quantitative survey. Data were collected from 500 elementary school teachers in Jambi Province, drawn from a population of 16,910 teachers. The sample size was determined using a sample size calculator with 95% confidence and a 4% margin of error. A 46-item questionnaire, adapted from established scales, was administered using a five-point Likert scale. Content validity was confirmed through expert review and the Content Validity Index (CVI), with all items exceeding 0.80. Data was analysed using Partial Least Squares Structural Equation Modeling (PLSSEM) with SmartPLS 4. The structural model shows that e-leadership has a positive and significant effect on school culture (β = 0.190; p < 0.001), teacher cooperation (β = 0.299; p < 0.001), and teacher performance (β = 0.288; p < 0.001). School culture (β = 0.266; p < 0.001) and teacher cooperation (β = 0.253; p = 0.002) also significantly enhance teacher performance. Teacher self-efficacy significantly predicts school culture (β = 0.683; p < 0.001) and teacher cooperation (β = 0.578; p < 0.001), but its direct effect on teacher performance is not significant (β = 0.109; p = 0.080). These results highlight the central role of e-leadership, school culture, and collaboration as key drivers of teacher performance, while self-efficacy operates mainly through indirect, contextual mechanisms.